Cost-comparison study of reusable and disposable rhinolaryngoscopes in a large English teaching hospital. Issue 5 (10th May 2023) - Morgan, O; Elsayed, M; Ramakrishnan, Y; McGlashan, J; Whynes, D; McCahon, R
Abstract: Objective: This study aimed to compare the cost per use of video-rhinolaryngoscopy using reusable and disposable devices in a tertiary referral centre. Methods: A cost-comparison study was performed that utilised retrospective cost data and prospective utilisation data to compare the total costs of using reusable video-rhinolaryngoscopes versus a single-use alternative. Results: It was estimated that 4776 and 1821 procedures were performed annually with reusable and disposable video-rhinolaryngoscopes, respectively. The cost per use was £66.61 for reusable devices versus £150.00 for disposable devices. The break-even point (i.e. when cost per use was equal, occurred at 1374 procedures per year). Thereafter, it was cheaper to use reusable devices. Conclusion: Disposable rhinolaryngoscopes may present a cheaper solution to services with low rates of rhinolaryngoscope utilisation. However, for larger services considering replacement of their reusable rhinolaryngoscopes with disposable units, it is likely that the recurring costs will be prohibitive in the medium to long term.